Importance of the C-Reactive Protein to Albumin Ratio in the Diagnosis and Prognosis of Mycosis Fungoides - Gamze Taş-Aygar; Hatice Ataş; Müzeyyen Gönül; Selda Pelin Kartal (Mattioli1885, 2024)
Introduction: CRP/albümin ratio (CAR) has been lately demonstrated as a prognostic factor and an indicator of disease activity, severity and prognosis in solid organ malignancies and inflammatory diseases. However, the effects of CAR have not been investigated in mycosis fungoides (MF) patients yet. This study aimed to determine the potential role of CAR as a diagnostic and a prognostic indicator in MF. Methods:We retrospectively investigated the electronic medical records of 97 patients with MF admitted to the Dermatology Clinic of Ankara Diskapi Yildirim Beyazit Training and Research Hospital between January 2014 and December 2020. In total, 60 patients with MF were enrolled in the study. CAR was evaluated, patient and control group. Also, the other clinicopathological factors including age, lactate dehydrogenase, stage of disease, beta-2-microglobulin levels, and sedimentation levels were evaluated. Results: The median value of CAR was 0.85 (0.10-7.51) in the patient group, whereas it was 0.39 (0.0-1.11)in the control group(P<0.001). Patients with disease progression (N:16, 13M, 3 F) had a median value of CAR 0.84 (0.10-7.51) and the median value of CAR (N:44) was 0.86 (0.12-4.57) in the group of patients with stable disease. The CAR value had no prognostic significance (P>0.05). Conclusion: There is no association between the CAR and progression in the stage in MF patients. But the CAR is significantly higher in patients with MF than in the control group. The CAR can be a guide for us in cases where we have difficulty in diagnosing.